Seberapa Efektifkah Booklet Materi Lapisan Atmosfer sebagai Peningkatan Hasil Belajar Geografi? - Nevy Farista Aristin; Karunia Puji Hastuti; Indra Setiawan; Sidharta Adyatma; Parida Angriani (Universitas Negeri Gorontalo, 2023)
The learning process communication deficiency is caused by the tendency to use media that still needs to be more effective. Learning media, such as booklets, supports the achievement of learning objectives. Experimental research with a nonequivalent control group design aims to determine the effectiveness of booklets on geography learning outcomes. Learning media booklet material for atmospheric layers is effectively used to improve the learning outcomes of class X students at SMAN 1 Alalak. Using booklet media for atmospheric layer material is effective, while conventional books could be more effective. So, it can be concluded that using booklets effectively improves the learning outcomes of class X students at SMAN 1 Alalak, Barito Kuala Regency. The results of this study may have implications for the increasing variety of innovative learning media to support the learning process in schools, especially high schools, which require atmospheric material booklets.